A PCR Test Using the Mini-PCR Platform and Simplified Product Detection Methods Is Highly Sensitive and Specific to Detect Fasciola hepatica DNA Mixed in Human Stool, Snail Tissue, and Water DNA Specimens. - Fernandez-Baca, M.V. (2024)
Fasciola hepatica has a complex lifecycle with multiple intermediate and definitive hosts and influenced by environmental factors. The disease causes significant morbidity in children and its prevalent worldwide. There is lack of data about distribution and burden of the disease in endemic regions, owing to poor efficacy of the different diagnostic methods used. A novel PCR-based test was developed by using a portable mini-PCR® platform to detect Fasciola sp. DNA and interpret the results via a fluorescence viewer and smartphone image analyzer application. Human stool, snail tissue, and water samples were used to extract DNA. Primers targeting the ITS-1 of the 18S rDNA gene of Fasciola sp. were used. The limit of detection of the mini-PCR test was 1 fg/μL for DNA samples diluted in water, 10 fg/μL for Fasciola/snail DNA scramble, and 100 fg/μL for Fasciola/stool DNA scramble. The product detection by agarose gel, direct visualization, and image analyses showed the same sensitivity. The Fh mini-PCR had a sensitivity and specificity equivalent to real-time PCR using the same specimens. Testing was also done on infected human stool and snail tissue successfully. These experiments demonstrated that Fh mini-PCR is as sensitive and specific as real time PCR but without the use of expensive equipment and laboratory facilities. Further testing of multiple specimens with natural infection will provide evidence for feasibility of deployment to resource constrained laboratories.